Therapy of Effective Progressive Muscle Relaxation to Reduce Insomnia in Elderly - Idris, Desi Natalia Trijayanti; Astarani, Kili (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Elderly experiencing problems sleeping disorders one of which is insomnia. One of the efforts to overcome insomnia is progressive muscle relaxation therapy. This study aims to analyze the effect of progressive muscle relaxation therapy on insomnia in the elderly. This research was designed using Pre Experimental, one group pre-test - post-test design. Data collected through observation and interviews before. It is analyzed using the Wilcoxon Signed Rank Test. The independent variable of this study was progressive muscle relaxation therapy and the dependent variable was insomnia. The results showed there was an effect of progressive muscle relaxation therapy with insomnia based on the Wilcoxon test (p = 0.004), and z score = 2.850. This study states that non-pharmacological therapy of progressive muscle relaxation therapy can be a nurse's independent action in providing nursing care to patients, especially in elderly patients who experience insomnia